Self-identified strategies to manage intake of tempting foods: cross-sectional and prospective associations with BMI and snack intake - Jennifer Gatzemeier; Laura L Wilkinson; Menna J Price; Michelle D Lee (Cambridge University Press, 2024)
Abstract Objectives: Individuals often use self-directed strategies to manage intake of tempting foods, but what these strategies are and whether they are effective is not well understood. This study assessed the frequency of use and subjective effectiveness of self-directed strategies in relation to BMI and snack intake. Design: A cross-sectional and prospective study with three time points (T1: baseline, T2: 3 months and T3: 3 years). At T1, demographics, frequency of use and subjective effectiveness of forty-one identified strategies were assessed. At T2 and T3, current weight was reported, and at T2 frequency of snack intake was also recorded. Setting: Online study in the UK. Participants: Data from 368 participants (Mage = 34·41 years; MBMI = 25·06 kg/m2) were used for analysis at T1, n = 170 (46·20 % of the total sample) at T2 and n = 51 (13·59 %) at T3. Results: Two strategy factors were identified via principal axis factoring: (1) diet, exercise, reduction of temptations, and cognitive strategies, and (2) planning, preparation and eating style. For strategy 1, frequency of use, but not subjective effectiveness, was positively related to BMI at T1. Subjective effectiveness predicted an increase in BMI from T1 and T2 to T3. No relationship to snack intake was found. For strategy 2, frequency of use was negatively related to BMI at T1. Neither frequency of use nor subjective effectiveness were related to changes in BMI over time, but subjective effectiveness was negatively correlated with unhealthy snack intake. Conclusion: Self-directed strategies to reduce the intake of tempting foods are not consistently related to BMI or snack intake.